2013
DOI: 10.1308/003588413x13511609957416
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trauma centre designation on open tibial fracture management

Abstract: INTRODUCTION The British Orthopaedic Association/British Association of Plastic, Reconstructive and Aesthetic Surgeons guidelines for the management of open tibial fractures recommend early senior combined orthopaedic and plastic surgical input with appropriate facilities to manage a high caseload. The aim of this study was to assess whether becoming a major trauma centre has affected the management of patients with open tibial fractures. METHODS Data were obtained prospectively on consecutive open tibial frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 6 publications
(5 reference statements)
0
41
1
Order By: Relevance
“…However, in the most recent period, the median time between fixation and soft tissue cover remained 2.5 days, and in 62% of cases, the delay from injury to soft tissue cover exceeded 72 hours and so failed to meet the BOAST 4 targets. Patients are therefore being transferred to our centre more quickly following the introduction of the MTC, as has been shown elsewhere, 2 and are having definitive fixation performed in our centre but there remained a delay in achieving soft tissue cover in period 3. The fall in the deep infection rate may reflect reduced time to surgery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in the most recent period, the median time between fixation and soft tissue cover remained 2.5 days, and in 62% of cases, the delay from injury to soft tissue cover exceeded 72 hours and so failed to meet the BOAST 4 targets. Patients are therefore being transferred to our centre more quickly following the introduction of the MTC, as has been shown elsewhere, 2 and are having definitive fixation performed in our centre but there remained a delay in achieving soft tissue cover in period 3. The fall in the deep infection rate may reflect reduced time to surgery.…”
Section: Discussionmentioning
confidence: 97%
“…2,3,8,10,11 However, there remains scope for expediting definitive soft tissue coverage both in our centre and in other MTCs through a process determined by local structural constraints. 12 The 'fix and flap' protocol is regarded as the gold standard for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stammers et al report similar improvements in open fracture management in the eight-month period directly following trauma centre designation. 9 The authors observed a reduction in time to soft tissue coverage approaching statistical significance from 199 to 89 hours (p=0.06). They attribute this to increased senior surgeon input, a dedicated major trauma theatre and prioritisation of joint cases.…”
Section: Fernandez Wallis Venus Skillman Young Costa the Impact Of A mentioning
confidence: 92%
“…9 The improvements in care observed may reflect a maturation of the major trauma centre, as care protocols, staff experience and processes become more effective, which drives down delays in definitive management and improves outcomes. 10,11 We believe that the intervention studied (a dedicated orthoplastic operating list) is part of the trauma centre maturation process, and separating the individual component effects of this and other procedural improvements on the management of open fractures becomes difficult.…”
Section: Fernandez Wallis Venus Skillman Young Costa the Impact Of A mentioning
confidence: 99%